Pelvic Inflammatory Disease: A Family Practice Perspective - Sellors, John W. (1989)
Most women with symptomatic acute pelvic inflammatory disease (PID) are now managed outside of hospital by private practitioners. Clinical diagnosis of PID is often inaccurate, but can be improved by knowledge of risk factors, use of simple investigations, and referral for laparoscopy when the physician is unsure. Prompt treatment with a recommended regimen that includes at least two antibiotics, careful consideration of when to hospitalize or refer, and an awareness of the need for compliance and follow up are important attributes of good management. In contrast, asymptomatic PID, which is a common antecedent of tubal factor infertility and ectopic pregnancy, can be prevented only by screening for and appropriate treatment of sexually transmitted infections.